THE INFLUENCE OF USING READ, ASK, PARAPHRASE (RAP) STRATEGY IN READING COMPREHENSION AT THE ELEVENTH GRADE STUDENTS OF SMK NEGERI LABUANG - Munawir, Ahmad; Umar, Umar; Ridwan, Ridwan; Safriani, Safriani (Study Program of English Literature, 2018)
The objectives of the research was to find out significant influence of using Read, Ask and Paraphrase(RAP) strategy to students’ reading comprehension at the eleventh grade students of SMK Negeri Labuang. The method of the research was quantitative method and the type of the research was pre-experimental research with one group pretest-treatment-posttest design. The total number of population was 6 classes and the total number of sample was 1 class consist of 26 students. The instrument of the research was as reading. The result of the data analysis show that the mean score in pretest (53,84) with standar deviation (14,01) is lower than the mean score in posttest (65) with standar deviation (12,08) and from the hypothesis, it is found that t-test value (2,79) is greater than t-table value (1.708). It is that null hypothesis (HO) is rejected and alternative hypothesis (H1) is accepted. It is included that using Read, Ask and Paraphrase (RAP) strategy in Reading Comprehension at the Eleventh Grade Students of SMK Negeri Labuang is effective to increase reading comprehension.